Submerged arc welding of low alloyed steel - Lee, Chee Sun. (2008)
A study has been carried out to evaluate the effect of welding parameters on the thermal attributes of the submerged arc welding (SAW) process such as the distribution of arc energy into the formation of weld metal and heat affected zone.